Pengembangan Media Interaktif Articulate Storyline dalam Pembelajaran Cerpen Kelas XI di SMK Negeri 1 Denpasar - Ajmadewi, Ni Putu Khrisna; Rasna, I Wayan; Artika, I Wayan (LP. Ma'arif Janggan Magetan, 2024)
This study aims to obtain an objective overview of the development of interactive media Articulate Storyline in learning short stories in class XI at SMK Negeri 1 Denpasar. This type of research uses Thiagarajan's 4-D development model, namely (1) define, (2) design, (3) develop, and (4) disseminate. However, due to time and cost limitations, research is only carried out until the develop stage. The results of the validity of the material showed that the interactive media Articulate Storyline developed obtained 97.7% material validity test results with very valid qualifications. The language validity test received a percentage score of 90.6% with very valid criteria. The validity test of the graphics obtained a percentage value of 93.7% with very valid criteria. The interactive media Articulate Storyline developed is in the practical category with a practicality score of 90% from teachers and 90.1% from students. The interactive media Articulate Storyline in learning short stories developed is quite effective in improving student learning outcomes. The results of the t-test showed a significance value of 0.000, smaller than the significance level of 0.05. This means that H0 is rejected or there is a significant difference in the average learning outcomes before and after being given learning treatment using Articulate Storyline interactive media. Furthermore, N-Gain calculations are carried out to determine the magnitude of the increase in learning outcomes in students. The acquisition of an N-Gain score of 0.59 means that there is an increase in student learning outcomes after learning with Articulate Storyline interactive media with a moderate improvement category.